Novel SPG10 mutation associated with dysautonomia, spinal cord atrophy, and skin biopsy abnormality. Issue 2 (12th July 2012) - Collongues, N.; Depienne, C.; Boehm, N.; Echaniz‐Laguna, A.; Samama, B.; Dürr, A.; Stevanin, G.; Leguern, E.; Brice, A.; Labauge, P.; de, J.
<x xml:space="preserve">Abstract</x> Background SPG10 is a rare form of autosomic dominant hereditary spastic paraplegia (HSP) caused by mutations in the KIF5A gene, which may be involved in axonal transport. Methods We report the characteristics of a French family with a novel missense mutation c.580 G>C in exon 7 of the KIF5A gene. Results The proband and his sister presented with an adult onset HSP, a sensory spinal cord‐like syndrome, dysautonomia, and severe axonal polyneuropathy. Contrary to the proband, his sister presented a secondary improvement in spasticity and walking. In the proband, MRI findings consisted in spinal cord atrophy and symmetric cerebral demyelination, whereas the skin biopsy suggested a defect in the number of vesicles and synaptophysin density at the pre‐synaptic membrane. Conclusion This study extends the phenotype of SPG10 and argues for abnormalities in the axonal vesicular transport.